PENERAPAN PRINSIP GOOD GOVERNANCE TERHADAP APARATUR DESA DALAM PELAYANAN PUBLIK DI DESA CIRO-CIROE KECAMATAN WATANG PULU KABUPATEN SIDENRENG RAPPANG - yenni jamal; Ahmad Mustanir; Adam Latif (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
The research objective was to determine the aplication of the principles of good governance to village officials in public services in the Ciro-ciroe village, Watang Pulu district, Sidenreng Rappang district and to determine the factors that influenca it. The population of this study was 1356 people, while the research sampel used total probability sampling amounting to 92 people. Data collectiontechniques used in this study are to use observation techniques, interviews, literature study and questionnaires. The data collected was then analyzed using frequency and percentage tables. The result sof this study indicate that the principles of good governance apparatus in the village of Ciro-ciroe Kacamatan Watang Pulu, Sidenreng Rappang Regency above, then the average percentage is obtained, namely 78,12%. So it can beconcluded that this indicatoris in the very good category. Public servants of the ciro-ciroe village apparatus Watang Pulu district Sidenreng Rappang district above, then the average percentage result it 69,83%. So it can be concluded that this indicator is in the quite good category. As for the factors that most influenca the application of the principles of good governance to village officials in public services in the Ciro-ciroe village Watang Pulu sub-district, Sidenreng Rappang district above, the average percentage result is 71,96%. So it can be concluded that this indicator is in the quite good category.